Estudo das características do aparelho reprodutivo, epitélio seminífero e mapas eletroforéticos bidimensionais do plasma seminal de carneiros Morada Nova - Sousa, Fabiane Maria Lima (2010)
Information on the reproductive physiological aspects about Morada Nova breed, especially for males, are still few and the lack of knowledge about that becomes a hindrance to implementation best management strategies and reproductive biotechnologies, based on this, this study aimed to describe the biometric characteristics of the reproductive tract in Morada Nova sheep as well as quantitative and qualitative aspects of spermato genesis and correlate them, and to characterize the electrophoretic maps of the seminal plasma of these animals. Semen was collected by electroejaculation in 15 male sheep of the Morada Nova breed, of which only 12 responded. The samples were centrifuged, for separation of seminal plasma , where it was used to determine of total protein concentration and protein profile by denaturing electrophoresis in polyacrylamide gel (SDS - PAGE). Biometric data were obtained from the testicles, epididymis and accessory s ex glands of the group of 15 animals that were slaughtered with an average age of 42 weeks and average weight of 28 kg. Immediately before slaughter, was taken to measure scrotal circumference (SC) of each animal . Then , the testicles, epididymis and access ory sex glands were weighed and measured individually (left and right). Testicles samples were fixed in Bouin's fluid for evaluation of seminiferous tubules. The testicular parenchyma was evaluated for diameter (TD), volume (VT) and length of seminiferous tubules, germinal epithelium height (EA) and a population of Sertoli cells and germinal cells. The proportion of testicular parenchyma occupied by seminiferous tubules was equivalent to 84.8 ± 0.1%. The overall yield of spermatogenesis was 59.8 ± 3.73 cell s. Each Sertoli cell (SC) was able to sustain 7.7 ± 0.51 round spermatids. Were realized analyses using Pearson correlation (p <0.05) between the studied characteristics and the variables were described as means and their respective standard errors using t he statistical program Statview, 5.0 (SAS, 2003). No difference was detected between the left and right values for any of the testicular parameters, epididymal and accessory sex glands. Significant correlations were found between weight and other measures testicle: length (TL), diameter (TD) and volume of parenchyma (VPAR) and other measures of reproductive tract as weight (PEP) and total length of the epididymis (TLE) and of body of the epididymis (LBEp). The testicular weight and diameter, were indicators of the reproductive function of the ram was correlated with all histologic described. For electrophoresis analysis, a total of 103 spots were identified, 45 these being present in all gels, and these spots presents in gel indicate the presence of importan t proteins in the seminal plasma. According to the results, measures of gonads showed correlations with the other structures of the reproductive tract and spermatogenic activity, and electrophoretic maps of seminal fluid were similar to Santa Inês sheep ad ults